Food loss and waste in agrifood systems: A review of the literature - Delgado, Luciana; Schuster, Monica; Torero, Máximo (International Food Policy Research Institute, 2021)
Tackling food loss and waste can help address hunger and malnutrition without adding to environmental stress. Reductions to food loss and waste also hold important implications for achieving the Sustainable Development Goals (SDGs) and transforming agrifood systems to make them more resilient, inclusive, and sustainable. However, the lack of country-level data and of an agrifood system-based approach has prevented countries from translating commitment into action to tackle the issue. This brief examines existing knowledge on food loss and waste in the context of agrifood systems. It concludes that food loss and waste pose multiple challenges, which can only be addressed through interdisciplinary research that considers all the elements of agrifood systems.